Profile of Young Entrepreneurs in Padang Sidempuan City (Case Study of Yoanisa Adhani Nasution, Young Entrepreneur in Padang Sidempuan City) - Hadji Hasibuan, Zul; Sunarti, Vevi (Universitas Negeri Padang, 2023)
This research is motivated by the success and efforts of Yoanisa Adhani Nasution in entrepreneurship. Researchers see that there are interesting and unique things in line with management and efforts to become entrepreneurs and develop their businesses in line with the needs and achievement of targets from an entrepreneur to becoming a successful entrepreneur. The research approach is qualitative, the type of case study research. The data sources in this study consisted of Yoanisa Adhani Nasution as the main subject and triangulation sources as additional informants so that the data or information found is more valid. Data collection techniques used are interviews, observation and documentation. The data analysis uses data reduction, data presentation, and drawing conclusions. The data validity uses observations, increasing persistence and triangulation sources and techniques. The results of this study indicate that the profile of young entrepreneurs in Padang Sidempuan City is very good in establishing a business, it can be seen from: (1) The selection of business fields is based on the main aspects, namely according to their interests and talents. (2) Creativity and innovation in entrepreneurship can be seen from ideas and renewal as well as business characteristics that make the business unique and how to develop ideas into business opportunities. (3) The driving factor for entrepreneurial success is based on the subject having expertise in the field of business, the hard work in establishing a business and seeing opportunities to be able to open a business. (4) The inhibiting factor as a challenge for entrepreneurship begins with the lack of capital to open a business.